178k views
0 votes
Find f(-3) if f(x) = x^2

User Duduwe
by
4.9k points

2 Answers

6 votes

Answer:

=

1

2

×

3

2

=

1

×

9

=

9

Step-by-step explanation:

f

(

3

)

=

9

Step-by-step explanation:

f

(

x

)

=

x

2

To find f(-3) replace

x

in the function by

3

Therefore:

f

(

3

)

=

(

3

)

2

=

1

2

×

3

2

=

1

×

9

=

9

User Jddsantaella
by
5.3k points
2 votes

Answer:

9

Step-by-step explanation:

f(x) = x²

f(-3) =(-3)² = (-3)*(-3) = 9

User FeRtoll
by
4.8k points